Tren Pembelajaran Bahasa Arab Menggunakan Aplikasi Interaktif di Tingkat Sekolah Menengah : Systematic Literature Review - Naurah Nazhipah Amalia; Farikh Ammar Marzuki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Arabic language learning in Indonesia is increasing in line with rapid technological advances. However, students' enthusiasm for learning Arabic is still relatively low, as they consider Arabic to be a complicated and boring subject. Interactive applications have emerged to address the challenges of Arabic language learning in schools, particularly at the junior high school/MTs and senior high school/MA levels. This study aims to identify the types of interactive applications frequently used in Arabic language learning at the junior high school/MTs and senior high school/MA levels, as well as to identify the benefits of using such applications. The research method employed was a Systematic Literature Review (SLR), analyzing selected articles obtained from the Garuda database. The analysis results show that there are six types of applications that are frequently used, namely Kahoot, WordWall, Canva, PowerPoint, Baamboozle, and Quizalize. The use of these applications has proven to increase students' interest, enthusiasm, and learning outcomes. Additionally, they enhance language skills and create a more enjoyable learning environment.